2021
DOI: 10.1186/s12909-021-03067-y
|View full text |Cite|
|
Sign up to set email alerts
|

Parental leave policy information during residency interviews

Abstract: Background During interviews, medical students may feel uncomfortable asking questions that might be important to them, such as parental leave. Parental leave policies may be difficult for applicants to access without asking the program director or other interviewers. The goal of this study is to evaluate whether parental leave information is presented to prospective residents and whether medical students want this information. Methods Fifty-two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ninety-two percent of respondents in a survey of medical students reported wanting parental leave policies to be formally presented in interviews and 68% reported feeling uncomfortable asking about parental leave. 35 Similarly, qualified faculty candidates could also feel uncomfortable asking about parental leave policies during the interview process, although it could be important to them when choosing a position.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-two percent of respondents in a survey of medical students reported wanting parental leave policies to be formally presented in interviews and 68% reported feeling uncomfortable asking about parental leave. 35 Similarly, qualified faculty candidates could also feel uncomfortable asking about parental leave policies during the interview process, although it could be important to them when choosing a position.…”
Section: Discussionmentioning
confidence: 99%
“…[the] institutional policy(ies) for vacation and leaves of absence, including medical, parental, and caregiver leaves of absence.” 7 Our data from both applicants and PDs suggest a meaningful number of programs have presented parental leave data verbally ( Table 4 ), despite many applicants citing hesitancy to broach the topic of parental leave due to perceived concerns of possible discrimination. 9 Verbal presentation may additionally have contributed to poor recollection of information presented. Based on the findings here, we encourage programs to maintain an updated program website and consider presenting parental leave policies in slide deck or handout materials in addition to their contract materials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that residency applicants seek information regarding work–life balance and that there is a need for improved transparency in communicating parental leave policies during the residency interview process. 9 , 10 Considering these national changes to parental leave policies that will affect future residents nationwide, we sought to characterize the state of parental leave policies in radiation oncology residency programs and examine how applicants prefer to obtain this information.…”
Section: Introductionmentioning
confidence: 99%
“…Correction to: BMC Medical Education (2021) 21:623 https://doi.org/10.1186/s12909-021-03067-y Following publication of the original article [1], we have been informed that the authors Jillian A. Maloney, Skye A. Buckner-Petty and Natalie H. Strand were incorrectly affiliated. Also, the affiliation address for the author Sharonne N. Hayes was incorrect.…”
Section: Open Accessmentioning
confidence: 99%